2022
DOI: 10.3390/polym14194008
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Friction and Wear Performance of PEK, PEEK and PEKK Binders in Tribological Coatings

Abstract: Tribological coatings are widely used in industry, particularly when the conventional oil lubrication of sliding surfaces has to be replaced by maintenance-free contacts. This work studies the tribological performance of waterborne tribological coatings based on three binders of the polyaryletherketone (PAEK) family: polyetherketone (PEK), PEEK, and polyetherketoneketone (PEKK). Even though PEEK is a well-known commercial solution for this type of tribological coatings, PEK and PEKK have never been studied in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 47 publications
0
0
0
Order By: Relevance
“…The components made from PEKK can withstand higher operating temperatures without losing structural integrity, this being one critical factor in the highperformance and longevity of robotic grippers, which often work in varied and demanding thermal environments (Tadini et al, 2017). Additionally, the robust carbon structure in PEKK provides excellent wear resistance, reducing the rate of material degradation under mechanical stress and repetitive motions, thereby extending the service life of the robotic grippers (Pedroso et al, 2022).…”
Section: Eds and Sem Investigationsmentioning
confidence: 99%
“…The components made from PEKK can withstand higher operating temperatures without losing structural integrity, this being one critical factor in the highperformance and longevity of robotic grippers, which often work in varied and demanding thermal environments (Tadini et al, 2017). Additionally, the robust carbon structure in PEKK provides excellent wear resistance, reducing the rate of material degradation under mechanical stress and repetitive motions, thereby extending the service life of the robotic grippers (Pedroso et al, 2022).…”
Section: Eds and Sem Investigationsmentioning
confidence: 99%
“…The study of tribological properties of materials has been and remains a relevant topic for scientists in various fields [21][22][23][24][25][26][27][28]. In order to reduce the level of friction force magnitude, various modifications are introduced in the material composition [24][25][26], lubricants are used [27], etc. [28].…”
Section: Problem Contextmentioning
confidence: 99%
“…Results showed that an increase in quantity was obtained using a laser power of 15 mW. Pedroso et al [16] investigated the tribological performance of waterborne tribological coatings based on three binders of PEEK and polyetherketone. Results suggested that PEKK and polyetherketone seem to be attractive alternatives to PEEK.…”
Section: Introductionmentioning
confidence: 99%